2002
DOI: 10.1021/ja012363k
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Synthetic Route of [35](1,2,3,4,5)Cyclophane, and Structural Properties of Multibridged [3n]Cyclophanes and Their Charge-Transfer Complexes in the Solid State1

Abstract: To develop an improved synthetic route to [3(6)](1,2,3,4,5,6)cyclophane (CP) 2, a more practical synthetic route to [3(5)](1,2,3,4,5)CP 3 than the original one was developed, which started from [3(2)](1,3)CP 7 via [3(4)](1,2,4,5)CP 5. The fundamental structural parameters of [3(n)]CPs (n = 3-6) in the solid state were elucidated, and the observed structures were in good agreement with the most stable conformers in solution and those predicted by the theoretical calculations. In the case of [3(6)]CP 2, the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 46 publications
3
42
0
Order By: Relevance
“…The TCNE adduct with 3 3 (1,3,5)cyclophane is reported to have a $\tilde \nu $ CN at 2134 cm −1 ,80 which suggests reduced TCNE, not TCNE 0 , as reported. Most likely this is a misprint, but perhaps it indicates formation of the electron‐transfer salt [3 3 (1,3,5)cyclophane] .+ [TCNE] .− , as also the dark purple color might indicate.…”
Section: Discussionmentioning
confidence: 69%
“…The TCNE adduct with 3 3 (1,3,5)cyclophane is reported to have a $\tilde \nu $ CN at 2134 cm −1 ,80 which suggests reduced TCNE, not TCNE 0 , as reported. Most likely this is a misprint, but perhaps it indicates formation of the electron‐transfer salt [3 3 (1,3,5)cyclophane] .+ [TCNE] .− , as also the dark purple color might indicate.…”
Section: Discussionmentioning
confidence: 69%
“…[19c] Upon revisiting this material it was reformulated as Cu 3 A C H T U N G T R E N N U N G (1,3,5)cyclophane is reported to have a ñ CN at 2134 cm À1 , [80] which suggests reduced TCNE, not TCNE 0 , as reported. Most likely this is a misprint, but perhaps it indicates formation of the electron-transfer salt [3 3 - …”
Section: Discussionmentioning
confidence: 91%
“…It has been well-known that cyclophane compounds possess the electron-donating ability to form the CT complexes with TCNQ. 18 On the other hand, the pyrene derivative with strong electron-donating groups, such as 1,3,6,8-tetrakis(dimethylamino)pyrene has also been reported to form CT complex with TCNQ efficiently. 19 We also confirmed that the CT complex formation of pyrene or CD2 with TCNQ by the absorption spectral change of pyrene or CD2 in the presence of TCNQ as shown in Figure 4.…”
Section: Ct Complex Formation With Tcnqmentioning
confidence: 99%